2015
DOI: 10.1007/s11695-015-1985-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin Secretion After Bariatric Surgery—Response to a Protein-Rich Mixed Meal Following Roux-En-Y Gastric Bypass and Sleeve Gastrectomy: a Pilot Study in Normoglycemic Women

Abstract: Gastrin secretion is diminished after RYGB. Hypergastrinemia was not present after SG, but a tendency of enhanced gastrin secretion was observed. These findings require further investigation in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…During our study, we encountered a few learning points, which, we hope, future researches planning similar research can benefit from and not run into the same problems. We based the feasibility of our protocol on previous studies detailing MMT after RYGB surgery [40,41]. In our study so far, a relatively large number (38 out of 134 participants) of participants exhibited adverse effects during the MMT at the one year after bariatric surgery (nausea, diarrhoea, dizziness and weakness).…”
Section: Lessons Learned So Farmentioning
confidence: 99%
“…During our study, we encountered a few learning points, which, we hope, future researches planning similar research can benefit from and not run into the same problems. We based the feasibility of our protocol on previous studies detailing MMT after RYGB surgery [40,41]. In our study so far, a relatively large number (38 out of 134 participants) of participants exhibited adverse effects during the MMT at the one year after bariatric surgery (nausea, diarrhoea, dizziness and weakness).…”
Section: Lessons Learned So Farmentioning
confidence: 99%
“…It has been suggested that excessive gastric acid production maybe involved in the pathogenesis of abnormal histological findings in the stomach after RYGB [ 10 ]. Grong et al used a protein-rich mixed meal on a cohort of 20 female patients previously operated with RYGB or SG versus 13 female matched controls and were able to demonstrate diminished gastrin levels in the RYGB but no statistically significant changes between the SG group and controls [ 11 ]. A study of 24 patients following GB demonstrated no change in fasting gastrin concentrations 6–12 months after surgery [ 12 ].…”
Section: Bariatric Surgery and Gut Hormonesmentioning
confidence: 99%
“…According to our study, we did not find evidence that hypergastrinemia might improve glucose control, as SHAM and EDG groups had similar level of plasma gastrin postoperatively, and yet only EDG group had glucose control improvements. Hypergastrinemia was also not found clinically following RYGB and SG procedures 48,49 , though one animal study suggested otherwise 50 . Furthermore, the effect of PPI on diabetes is still controversial, as one study did not found improvements on the glycated haemoglobin following interventions 51 .…”
Section: Discussionmentioning
confidence: 99%